Milk performance of dairy cows supplemented with a combination of slow-release nitrogen and exogenous fibrolytic enzyme - Sharma, Vimlesh C; Singh, Sudhir K; Mahesh, M S; Atmakuri, Srilatha; Chandran, B; Balakrishnan, U (Indian Journal of Dairy Science, 2021)
The purpose of this on-farm trial was to evaluate the impact of supplementing slow-release nitrogen (SRN; min. 40% N) and exogenous fibrolytic enzyme (EFE; cellulase, xylanase, glucanase, mannanase and xylanase-potentiating factor) products on milk yield and composition in dairy cows. Twelve early-to-midlactating crossbred cows were divided into 2 groups with comparable milk production. Animals were fed on a total mixed ration comprising of green maize, wheat straw and concentrate mixture. Group T1 was supplemented with urea at 80 g/animal/d, whereas that of T2 received a novel combination of cellulo-polymer-coated SRN at 80 g and EFE at 4 g/animal/d for a period of 20 days. Results showed no difference in milk yield (13.8 vs. 15.1 kg/d; P=0.559) between the groups; however, milk fat (3.49 vs. 3.87%) and solid not fat (7.92 vs. 8.35%) levels were higher (P